Taxonomy and phylogeny of Koinocystididae (Platyhelminthes, Kalyptorhynchia), with the description of three new genera and twelve new species - Diez, Yander L.; Monnens, Marlies; Aguirre, Rosa Isabel; Yurduseven, Rana; Jouk, Philippe; van Steenkiste, Niels W. L.; Leander, Brian S.; Schockaert, Ernest; Reygel, Patrick; Smeets, Karen; Artois, Tom (Zootaxa, 2021)
The taxon Koinocystididae is the third most species-rich family within Eukalyptorhynchia. However, its diversity and phylogeny have been largely neglected in former studies. We introduce three new genera and twelve new species of Koinocystididae including Simplexcystis asymmetrica gen. n. sp. n., Galapagetula cubensis sp. n., eight species of Reinhardorhynchus gen. n. and two species of Itaipusa. This raises the total number of species within Koinocystididae from 51 to 63. We also report on new distribution records for six known species: I. divae (Cuba, Panama and New Caledonia), I. karlingi (Sardinia and Lanzarote), Reinhardorhynchus riegeri comb. n. (Cuba), R. ruffinjonesi comb. n. (Cuba and Panama), Utelga heinckei (Cuba and Lanzarote), and U. pseudoheinckei (Sardinia). Simplexcystis asymmetrica gen. n. sp. n. is characterised by a male duct running eccentrically through the copulatory bulb, lack of any hard structures in the male system, lack of a bursa, and the fact that the epithelia of the female, the male, and part of the common atrium are covered by a brush border. Galapagetula cubensis sp. n. has a caudal gonopore, a divisa-type copulatory bulb with an unarmed penis papilla, and a female duct without a sphincter. The new species of Itaipusa and Reinhardorhynchus gen. n. differ from their congeners in the detailed structure of the copulatory bulb and especially the hard structures associated with it. In a molecular phylogenetic analysis based on all available 18S and 28S rDNA sequences of koinocystidids, we found support for the monophyly of the family and the genus Utelga Marcus, 1949. The genus Itaipusa is not monophyletic in that I. sinensis forms a clade with Rhinolasius dillonicus, while other species of Itaipusa that have a copulatory bulb armed with hooks form a clade together with Sekerana stolzi. As the type species of Itaipusa (I. divae) is in neither of these clades, we erected a new genus for I. sinensis (Koinogladius gen. n.) and one for species of Itaipusa having a hook-bearing copulatory bulb (Reinhardorhynchus gen. n.), respectively. Whether the remaining species of Itaipusa form a monophylum remains uncertain.